RNAseq analysis for the diagnosis of muscular dystrophy. Issue 1 (8th December 2015) - Gonorazky, Hernan; Liang, Minggao; Cummings, Beryl; Lek, Monkol; Micallef, Johann; Hawkins, Cynthia; Basran, Raveen; Cohn, Ronald; Wilson, Michael D.; MacArthur, Daniel; Marshall, Christian R.; Ray, Peter N.; et al.
Abstract: The precise genetic cause remains elusive in nearly 50% of patients with presumed neurogenetic disease, representing a significant barrier for clinical care. This is despite significant advances in clinical genetic diagnostics, including the application of whole‐exome sequencing and next‐generation sequencing‐based gene panels. In this study, we identify a deep intronic mutation in the DMD gene in a patient with muscular dystrophy using both conventional and RNAseq‐based transcriptome analyses. The implications of our data are that noncoding mutations likely comprise an important source of unresolved genetic disease and that RNAseq is a powerful platform for detecting such mutations.